Evaluation of Acidity Constants and Evolution of Electronic Features of Phenol Derivatives in Different Compositions of Methanol/Water Mixture - Mahmood Sanchooli (Journal of Chemistry)
This work was devoted to evaluation of acidity constants of 28 phenol derivatives in 11 different compositions of methanol/water solvent mixtures. The Onsager reaction field model was applied to any molecule of phenol derivatives dissolved in binary mixture of methanol/water, and the quantum chemical descriptors of the solute were calculated. Multiple linear regression was used to perform the reliable QSPR models in order to predict the acidity constants of the solutes. It was explored that the solvation of phenol derivatives in solvent of binary mixture of methanol/water shows a different behavior as the composition of methanol varies. Four different mechanisms proposed for solvation in 0–100 volume percent of methanol solvent. It was seen that the dipole-dipole interactions increase as the amount of methanol increases in solvent mixture, which implies the contribution of highly negative oxygens of methanol on hydrogen bondings between solute and solvent cavity. The orbital energies are a major electronic descriptor on solvation processes. This proposes that the charge exchange between frontier orbital energies of anions and the solvent molecules is the major event occurring in solution in order to stabilize the produced anions.